The Design Of Garment Enterprise Data Warehouse Using The TOGAF Framework - Merta Suryani, Ni Putu Sri; Sukadiana Putra, Putu Bagus Indra; Saputra, Komang Oka (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Garment company is a company that is recycling fabric into apparel. Processing through several phases i.e. Setup process materials, production planning to produce a product. In the garment companyhas units that administered by the manager. The unit i.e. warehouses, production, marketing, human resources and finance. As time goes by, followed by information technology which is increasingly growing, the company needs a system of information that is in tune with the business processes of the company. For it takes a data warehouse technology, so need to built an integrated information system between units. Enterprise Architecture is the method used in building an enterprise architecture. One of the frameworks used in building an information system is TOGAF. TOGAF is used as a step in establishing a system of information in the future can support the business activities of the company.